2013
DOI: 10.1371/journal.pone.0058616
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Assessment of Enthesitis in HLA-B27 Positive Patients with Rheumatoid Arthritis, a Matched Case-Only Study

Abstract: IntroductionHLA-B27 has a modifier effect on the phenotype of multiple diseases, both associated and non-associated with it. Among these effects, an increased frequency of clinical enthesitis in patients with Rheumatoid Arthritis (RA) has been reported but never explored again. We aimed to replicate this study with a sensitive and quantitative assessment of enthesitis by using standardized ultrasonography (US).MethodsThe Madrid Sonography Enthesitis Index (MASEI) was applied to the US assessment of 41 HLA-B27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 42 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…Certain types of HLA antigens are more frequent in some diseases. Studies on patients with rheumatic diseases can be given as examples (12,13). Osteoarticular involvement is a frequent and treatable complication of brucellosis.…”
Section: Discussionmentioning
confidence: 99%
“…Certain types of HLA antigens are more frequent in some diseases. Studies on patients with rheumatic diseases can be given as examples (12,13). Osteoarticular involvement is a frequent and treatable complication of brucellosis.…”
Section: Discussionmentioning
confidence: 99%
“…The research by Toussirot et al [ 4 ] shows that 6.6% of patients with RA may have positive HLA-B27, which is comparable to the general population, wherein the expression of this antigen is 5–8%. The presence of HLA-B27 in patients with RA does not increase the incidence of enthesitis or sacroiliac joint inflammation [ 4 , 8 , 9 ]. The percentage of people with positive HLA-B27 who can develop AS did not exceed 5%, whereas this antigen is detected in up to 90–95% of Caucasians suffering from AS [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies by other investigators regarding the specificity of these imaging findings, reviewed recently by Paramarta, et al 10 , yielded conflicting results. Additional support for the importance of enthesitis in SpA pathology indicated that HLA-B27+ patients with plantar fasciitis demonstrated more severe bone pathology (bone marrow edema) than HLA-B27-negative patients 11 ; and in an ultrasound assessment of patients with established RA, the presence of HLA-B27 alleles was not associated with increased prevalence of enthesitis, suggesting that additional factors, not observed in this population, are required for the enthesis phenotype to be expressed 12 .…”
Section: Enthesitis: a Cardinal Event In Psoriatic Arthritis?mentioning
confidence: 95%